ダイ35ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク1993-1994 - 渡辺, 興亜; ワタナベ, オキツグ; Watanabe, Okitsugu (1997)
P(論文) 第35次南極地域観測隊夏隊16名(渡辺興亜観測隊長), 交換科学者3名および越冬隊(横山宏太郎越冬隊長)40名は1993年11月14日「しらせ」にて日本出航, オーストラリアを経て, 南極, 昭和基地に向かった。当年の昭和基地近辺の海氷は, 「しらせ」の航行にとって極めて困難な状況にあった。昭和基地まで約10海里の地点に達するまでに計画日程から大幅に遅れ, しかもそれから先の砕氷航行は極めて困難な状況で, 結局昭和基地接岸を断念した。第35次隊の夏期行動では多くの観測, 設営計画があり, こうした状況での, その完全実施は困難な状況にあったが, 空輸, 氷上輸送とも順調に進み, 計画量の96%の輸送を達成し, 第35次隊の越冬計画に支障の無い程度にまで持ち直すことが出来た。しかし, 夏期の建設計画や内陸基地への輸送計画は大幅な計画変更を余儀なくされた。夏期の観測計画は最小限の変更に留めた。リュツォ・ホルム湾を離れてからの帰路の観測は順調に推移し, 中国, 中山基地に立ち寄った後, 往路に引き続き, 帰路の船上観測を実施しつつ, シドニーに到着, 1994年3月28日に空路帰国した。 The 35th Japanese Antarctic Research Expedition (JARE-35) consisted of forty wintering members and sixteen summer members plus three foreign scientists from the U.S.A. and Australia. The icebreaker SHIRASE left Tokyo on November 14,1993,and arrived at the pack ice edge near Lutzow-Holm Bay on December 17. Due to unusually severe sea ice conditions, continuous icebreaking began at this point, and continued until finally the icebreaker SHIRASE was stalled 10 nautical miles away from Syowa Station. At this point, the expedition stores were transferred to Syowa Station by helicopter airlift and snow vehicle through sea ice route. These operations transported more than 96% of the total expedition baggage. Under these circumstances, logistic operations such as construction and replacement of buildings and facilities did not progress on schedule. Observations on geology, geography, geodesy, biology and others were also not completed. However, after the ship left the pack ice in Lutzow-Holm Bay and along the Prince Olav Coast, the observations of physical and chemical oceanography, marine biology and earth sciences were made according to the program. The icebreaker arrived at Sydney on March 21,1994. Expedition members and the wintering party of JARE-34 returned to Japan in March 28. departmental bulletin paper